Formal variability in Fishtail Projectile Points of Amigo Oeste archaeological site, Plateau (Río Negro, Argentina) - Hermo, Dario Omar; Terranova, Enrique Daniel
Los Dos Amigos (LDA) archaeological locality is distinguished by the presence of a particular geological formation, two islan hills, called Amigo Oeste (AW) an Amigo Este (AE), related by afloor or open area and a gully (LDA 5). The site called Amigo West (AW) es of great importance in the region. In this hill was found a lithic assemblage composed of more than one hundred fishtail points (FTP), vifaces, knives and marginally retouched tools, and a large numbers of others artifacts that correspond to the sequences of manufacturing, ractivation, recycling and replacement of the FTP. This papers presents a techno-morphological characterization of the FTP an other bifacial artifacts associated, based on the description of its formal attributes. Fil: Hermo, Dario Omar. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Terranova, Enrique Daniel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina